Avoidance-related behavioral and blood-based physiological responses of Nguni and Boran cattle subjected to routine handling activities post relocation - Slayi, Mhlangabezi (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the avoidance-related behavioral and blood-based physiological responses of Nguni and Boran cattle during routine handling activities post-relocation, with a particular focus on the effect of breed, week, and waiting time. A total of 20 animals, 10 from each breed, were subjected to handling activities at fortnight intervals post-relocation. The animals were observed for entry time (ES), chute score (CS), kicking score (KS), blood sampling time, cortisol, and glucose concentrations. The data were analyzed using ANOVA and regression analysis. Results showed that breed had a significant effect on avoidance-related behavioral responses (ES: P=0.0032; CS: P=0.0071; and EX: P=0.0320), with Nguni cattle displaying more active avoidance behaviors compared to Boran cattle. Additionally, breed differences were observed in physiological responses, with Nguni cattle exhibiting higher cortisol and glucose levels compared to Boran cattle. Waiting time in the race had a greater impact on chute score (CS: P=0.0037) and cortisol release (P=0.0375) in the two breeds. Regression analysis revealed that the amount of time spent in the handling facility prior to sampling and the duration of blood collection significantly increased from week 3 to 15. Steers that waited in the race for more than ten minutes had higher cortisol levels (P=0.0031). These findings suggest that breed-specific management practices may be necessary to reduce stress-related responses and improve animal welfare during routine handling activities post-relocation. Overall, this study highlights the importance of considering the effects of breed, week, and waiting time when evaluating the avoidance-related behavioral and blood-based physiological responses of cattle during routine handling activities. These factors play a significant role in understanding and addressing the stress and welfare concerns associated with handling procedures, particularly after relocation.